Persepsi Masyarakat Tentang Peran Surau Di Kenagarian Koto Kaciak Kecamatan Bonjol Kabupaten Pasaman - Silvia, Ade - (Pendidikan Geografi, 2014)
This Reseach ims to gain an overview of the public perception of the role of the Surau viewed from: 1). The role of the Surau then and now, 2). The cause of the loss of the role of the Surau 3) Efforts to restore the role of the Surau. The research is a qualitative, the subject of this study through purposive sampling data were collected through 1). interview 2). observation. Informants in this study is a public figure, people living around village Koto Kaciak, surau committee is key informants surau committee. Testing the validity of the data in this study was conducted with data reduction, data presentation, interpretation of data, and conclusions. The research results village Kaciak Koto subdistrict Bonjol Pasaman found that: 1). Role surau past and present together as a community of worship formerly the surau droves, but at the present time at least pilgrims coming the surau, which come only old people while the younger generation has rarely come the surau even say never again. 2). The cause of the loss of the role of the surau in village Kaciak Koto, the existence of the times, technology, family factors, factors influx of foreign culture into the society, and economic factors. 3). Efforts to restore the role of the Surau, conducted deliberation Indigenous leaders and religious leaders, held a teen wird recitation, restore function niniak mamak as to which function, mental construct grandchildren nephew, the Government invites village existing traditional institutions such in village Bamus, KAN and the village particularly furnace tigo sanjarangan, niniak mamak, scholars, cadiak pandai Community. especially young people socialize important switch roles as first mosque in fostering and educating morals, attitudes and behavior of young people at the present time.